IMPLEMENTASI KEBIJAKAN PENGEMBANGAN DESTINASI WISATA DI KABUPATEN GRESIK TAHUN 2017 - Sari, Hajar Ratna (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
Implementation of tourism destination development policy in Gresik Dsitrict in 2017. This study aims to determine the implementation of development policy of tourist destinations in Gresik regency. The reason this research is conducted is the potential of tourism destinations that support to be used as a place of tourism. The purpose of this study was conducted to find out how the implementation of tourism destination development in Gresik regency as well as to know what factors that drive and hinder the implementation of tourism destinations development in Gresik regency. This research uses descriptive research method using qualitative approach. Data collection using observation techniques, interviews, documentation and literature study. The results of this study indicate the existence of existing tourist destinations in Gresik regency management has not been perfected by Dinas Pariwisata dan Kebudayaanbecause of the status of land that still belongs to the village. The driving factor for the development of tourist destinations is tourism potential in Gresik regency proper to be developed into tourism area. While the inhibiting factor is the problem of management that is constrained by the status of land still belongs to the community. Â Keywords: Implementation, tourist destination, Gresik regency